Aḥmadu Bamba and the Preceding Sufi Heritage: Tracing the Intellectual Sources of Bamba’s Sufi Writings - Khadim Cheikhouna Mbacke (Tasavvuf Araştırmaları Enstitüsü Dergisi)
This study examines the intellectual formation of Aḥmadu Bamba Mbacke (d. 1927), founder of the al-Murīdiyya Sufi order in Senegal, whose teachings have significantly shaped West African Islamic thought and practice. While the socio-political influence of al-Murīdiyya has been widely acknowledged, the intellectual foundations of Bamba’s Sufi thought remain insufficiently explored. This research hypothesizes that Bamba’s thought was profoundly shaped by classical Sufi figures such as Abū Ḥāmid al-Ghazzālī (d. 505/1111), ʿAbdu-l-Wahhāb ash-Shaʿrānī (d. 973/1565), Aḥmad Zarrūq (d. 899/1493), Ibn ʿAtāʾ Allah as-Sakandarī (d. 709/1309), as well as Mauritanian scholars including Sīdī Mukhtār al-Kuntiyyu (d. 1226/1811) and Muḥammad ibn al-Mukhtār ad-Daymānī (d. 1166/1753). Notably, Bamba distanced himself from speculative and philosophical Sufism, instead emphasizing a practical, ethically grounded Sufism centered on spiritual discipline, moral reform, and communal service. Through textual analysis and historical contextualization, this study investigates how these intellectual and spiritual currents informed Bamba’s synthesis of Sufi pedagogy and reform, contributing to a localized yet universal model of Islamic spirituality.